Behaviour of Market Arrivals and Price of Groundnut in Tamil Nadu : An Economic Analysis - Muthuraj, M. (Arthshastra Indian Journal of Economics & Research, 2017)
India ranked 2nd in the world groundnut production after China, with an annual groundnut seed production of 5.9 million tonnes and annual groundnut oil production of 1.5 million tonnes in 2015. In India, Tamil Nadu is one among the leading groundnut cultivating states. Groundnut cultivation covers 5.9% of the area and 4.3% of production. Among different districts in Tamil Nadu, Thiruvannamalai District is the most important producer of groundnut. The present study measured the monthly time-series data on indices of seasonal indices of arrivals and prices of groundnut for the year 2015. I found that the price was the only factor which determined the quantity of market arrivals in the short run. It was also found that the trend in arrivals and prices were found to be positive over a period of time. The growth rates were estimated to be 3.81% for the arrivals and 12.07% for the prices of groundnut. This indicated that the percentage increase in prices of groundnut was found to be higher than that of arrivals.